The Halal Tourism Trajectory, the Emergence and Challenge: The Case of Nanggroe Aceh Darussalam Post-2004 Tsunami - Erda Rindrasih (Humaniora, 2021)
Halal tourism has attracted a lot of attention in contemporary tourism and hospitality research. However, only a few studies have attempted to understand the emerging process and challenges in practicing halal tourism in a specific geographic location. This study aimed to investigate the new, emerging halal tourism that has been taking place in Aceh, following the tsunami that struck it in 2004. The research was based on fieldwork conducted in 2016 and 2017 in Aceh, using interviews and focus group discussions with tour guides, tour agents, community members, and the local government. Additional online interviews were performed in 2020. The results suggest that the new niche of ‘halal tourism’ is driven not only by the market, but the community, as well. Moreover, the implementation of halal tourism under Aceh’s Sharia Law has been challenged by both internal and external factors. Internally, it is challenged by the risk of natural disasters, risks of political instability, and institutional managerial problems. Meanwhile, externally, practicing halal tourism is challenged by the misperceptions of Islam (Islamophobia) and the marketing label.